MAKNA PERSEKUTUAN ORANG PERCAYA BERDASARKAN YOHANES 13:34-35 DALAM PERSPEKTIF TEOLOGI DAN SOSIOLOGI KRISTEN - Degyani Tandi Lamma; Dewi Ratte Barri; Dila Matira; Rikayani Ala'; Jein Retnawati; Ryanto Tangibali (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to analyze the meaning of the fellowship of believers based on John 13:34–35 from the perspectives of Christian theology and sociology. Employing a qualitative method with a library research approach, the study analyzes the biblical text alongside relevant theological and Christian sociological literature. The findings indicate that Jesus' command to love one another serves as the primary foundation for the formation of the fellowship of believers. Theologically, this fellowship is a manifestation of God's love—revealed through Christ and embodied in the life of the church as the body of Christ. Meanwhile, from a Christian sociological perspective, the fellowship functions to build solidarity, strengthen social integration, shape character, and foster concern for society. The practice of love as taught in John 13:34–35 transforms the church into not merely a community of faith but also an agent of social transformation that brings peace, service, and Christian witness to society. Thus, love becomes the cornerstone of the fellowship's life, strengthening the church's identity while enhancing the relevance of Christian ministry in addressing the various challenges of social life.